A Visibly Observable, Programmable Supramolecular Logic Platform and Its Application in Smart Thiols Sensing. Issue 22 (22nd March 2019) - Chen, Jianchi; Yang, Shu; Yang, Chunrong; Li, Jicheng; Huang, Dan; Lin, Xiao; Guo, Chen; Zhou, Qiuju; Yang, Qianfan; Tang, Yalin
Abstract: Molecular computation is increasingly attractive as a tool for medical and biological research because of its programmability and controllability. Herein, a novel visibly observable supramolecular system that can execute multi‐level logic functions on a uniform platform was constructed. By employing some programming factors, we succeeded in not only constructing a whole set of contrary logic pairs, but also building up a logic network that can implement advanced functions. Further, the platform is applied to sense thiols in specific environments. The developed method can efficiently filter signals of thiols in intracellular conditions and measure cysteine levels quantitatively in serum conditions. The visual readout makes the method particularly suitable for point‐of‐care testing. The supramolecule‐based platform illustrates not only an incremental advance for the construction of programmable molecular logic systems, but also viable applications in intelligent thiol analysis. Abstract : Chemical computer : A novel logic platform was constructed based on a programmable supramolecular system, which could implement the complete set of contrary logic pair functions and further be integrated into a network pattern to execute advanced operations, possessing great potential for practical application.